Is community forestry of Nepal’s Terai in right direction ? - Baral, Jagadish Chandra; Subedi, Bodh Raj (Banko Janakari, 2017)
The paper which is based on the study visit of twenty districts of the Terai has attempted to describe some discrepancies of community forestry in the region. Although, it is argued that the trend of forest degradation has decreased since handover, but at the same time a number of unintended social anomalies have also arised. Such anomalies essentially constitute of inequity and unfairness in the local and national level and in terms of long-term sustainability of forest resources. To minimise such irregularities a steady and 'process oriented' handover is suggested instead of those based on inadequate field works.